Suppose f'(2)=3, f'(5)=4 and let h(x) be the composite function h(x)=f( +1). Find h'(2). Do I need a formal proof and stuff?
Follow Math Help Forum on Facebook and Google+
Originally Posted by tn11631 Suppose f'(2)=3, f'(5)=4 and let h(x) be the composite function h(x)=f( +1). Find h'(2). Do I need a formal proof and stuff? all you need is the chain rule ...
The reason I asked if it need a proof, and posted in the analysis section was because its out of an into to applied analysis book..but thank you!